Clinical assessment and comparison of annotation algorithms in high‐density mapping of regular atrial tachycardias. (10th November 2017) - De Pooter, Jan; El Haddad, Milad; Wolf, Michael; Phlips, Thomas; Van Heuverswyn, Frederic; Timmers, Liesbeth; Tavernier, René; Knecht, Sebastien; Vandekerckhove, Yves; Duytschaever, Mattias
Abstract: Background: High‐density automated mapping of regular atrial tachycardias (ATs) requires accurate assessment of local activation times (LATs). Objective: To evaluate high‐density mapping of ATs and compare the accuracy of different automated LAT annotation algorithms. Methods: Fifteen patients underwent AT ablation guided by the automated ConfiDENSEۛ high‐density mapping module (Carto 3 v4) allowing manual reannotation (edited maps). For each AT, unedited automated maps were reconstructed offline by three algorithms: maximum unipolar slope (LATSlope ), bipolar peak (LATPeak ), and a new hybrid annotation algorithm (LATHybrid ). Five blinded experts were asked to define the (1) tachycardia mechanism, (2) ablation target, and (3) level of difficulty of these unedited maps. Results: Twenty‐one ATs (cycle length 300 ± 46 ms, activation points 955 ± 421) were successfully ablated using LATHybrid guided ablation with manual editing in a small number of points. At 6 months, 14 (93%) of the patients were free of AT recurrences. Unedited LATHybrid maps showed the highest accuracy in defining the tachycardia mechanism (LATHybrid : 49% vs. LATPeak : 27% vs. LATSlope : 28%, P < 0.001) and ablation target (LATHybrid : 65% vs. LATPeak : 39% vs. LATSlope : 31%, P < 0.001). Overall, LATHybrid ‐annotated maps were graded as "easier to interpret" by the experts (difficulty score 2.3 ± 0.9) versus LATPeak (2.8 ± 1) and LATSlope (3.2 ± 0.8) (P < 0.001). Only 12% of the LATHybrid maps were annotated as uninterpretable compared to 31% of LATSlope and 45% of the LATPeak maps (P < 0.001). Conclusion: Automated LATHybrid annotation allows better and easier recognition of the tachycardia mechanism compared to automated LATPeak and LATSlope algorithms, although fully automated mapping still requires further improvements.